A Goals-Based Theory of Utility. Issue 1 (2nd January 2021) - Parker, Franklin J.
Abstract: Theoretical frameworks to date have prescribed how an investor should allocate wealth within mental accounts. However, there is no fully cohesive solution to prescribe how an investor should rationally allocate resources across mental accounts. It is the aim of this discussion to fill that theoretical gap. We present a framework which can be used to rationally allocate resources both within and across mental accounts or goals. We then compare and contrast this method with mean-variance optimization and behavioral portfolio theory, showing that both are stochastically dominated by the goals-based utility framework. In further analysis of empirical validity, we discuss the Samuelson Paradox, Friedman-Savage puzzle, and probability weighting functions.